The Effects of Reducing the Entitlement Period to Unemployment Insurance Benefits - Nynke De Groot; Bas van der Klaauw (Institute for the Study of Labor (IZA), 2014)
This paper exploits a substantial reform of the Dutch UI law to study the effect of the entitlement period on job finding and subsequent labor market outcomes. Using detailed administrative data covering the full population we find that reducing the entitlement period increases the job finding rate, but decreases the job quality. Unemployed workers accept more often temporary jobs with lower wages and fewer working hours. Therefore, they also change jobs more frequently. The reform did not affect total post-unemployment earnings indicating that the positive effects on job finding and job turnover cancel out the negative effects on job quality. We also observe a spike in job finding around benefits exhaustion even, although more modest, for individuals who do not experience a drop in benefits level when moving to welfare.
Keywords: J64; J65; C21; C41; 330; unemployment benefits entitlement; job finding; job quality; difference-in-differences; duration model